TINDAK TUTUR EKSPRESIF PADA KANAL YOUTUBE DENNY SUMARGO EPISODE “DILAN JANIAR DISELINGKUHI DENGAN PULUHAN WANITA”:KAJIAN PRAGMATIK - Hijja, Nurul; Usman; Anita Candra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study employs a descriptive qualitative approach to examine the forms of expressive speech acts that appear in conversations within Denny Sumargo’s YouTube podcast videos. The research applies the listening method with a note-taking technique, which involves observing the spoken utterances delivered by the host and the guest, then recording data relevant to the research objectives. The data source consists of spoken utterances that are transcribed verbatim from the interactive dialogues between the host and the guest in the podcast videos. Data analysis is conducted using the interactive analysis model proposed by Miles and Huberman, which comprises three main stages: data reduction, data display, and conclusion drawing and verification. During the data reduction stage, the researcher selects and simplifies utterances that contain expressive speech acts. Subsequently, the data are presented in the form of descriptive narratives and matrices to facilitate understanding. The final stage involves drawing conclusions based on the patterns and tendencies identified in the data.The results indicate that there are five dominant types of expressive speech acts, namely expressing gratitude, apologizing, blaming, praising, and expressing condolences. Among these types, blaming speech acts are the most dominant. These speech acts are used by the guest to express emotions of disappointment, anger, and dissatisfaction related to personal experiences. The findings demonstrate that the conversations in the podcast are rich in authentic emotional expressions and reflect the psychological condition of the speakers. Theoretically, this study reinforces Searle’s theory of expressive speech acts. In addition, the findings are expected to contribute to the development of pragmatic studies, particularly in the analysis of digital communication content on YouTube, and to serve as learning material for linguistics and mass communication.